2012
DOI: 10.1017/s1468109911000235
|View full text |Cite
|
Sign up to set email alerts
|

A Deliberative Approach to Northeast Asia's Contested History

Abstract: AbstractThe failure to reconcile views of the past and to address historical injustice has damaged inter-state relations in Northeast Asia. Joint committees, dialogues, and the participation of civil society have been used to address historical issues, but scholars in the disciplines of international relations and area studies have largely ignored these dialogues and deliberative forums. At the same time, there is an emergent theoretical literature on how deliberative democracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Literature has shown that in many cases these people's opinions on given public issues changed significantly before and after the process. The method has been applied successfully even in authoritarian societies (see the experiences in the PRC, called "authoritarian deliberation" by He and Warren, 2011; see also Fishkin et al, 2010;He and Hundt, 2011;Hsu, 2009). For the description of the other models, see the survey in Smith (2011).…”
Section: Notesmentioning
confidence: 99%
“…Literature has shown that in many cases these people's opinions on given public issues changed significantly before and after the process. The method has been applied successfully even in authoritarian societies (see the experiences in the PRC, called "authoritarian deliberation" by He and Warren, 2011; see also Fishkin et al, 2010;He and Hundt, 2011;Hsu, 2009). For the description of the other models, see the survey in Smith (2011).…”
Section: Notesmentioning
confidence: 99%
“…When a portion of voters did not like the idea of 'Asianization of Australian life' , the Howard government slowed down the process of engagement with Asia. Moreover, Japan and South Korea are both democracies, but their conflict over history textbooks inhibits the development of regionalism in northeast Asia (He and Hundt, 2011).…”
Section: The Awkward Role Of Democracymentioning
confidence: 99%
“…The Northeast Asia sub-region has also played host to a range of initiatives by non-state actors. For instance, history researchers from China, Korea, and Japan have collaborated on bilateral and trilateral bases to arrive at common understandings of regional history (He and Hundt, 2011), while transnational links between civil society actors in sectors such as the environment are also substantial.…”
Section: Thinking About Regionalismmentioning
confidence: 99%